Early stages of the ‘his genitive’: Separated genitives in Old English - Pérez Lorido, Rodrigo; Casado Núñez, Patricia (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2019)
In this paper we provide new evidence to demonstrate that the ‘his genitive’ or ‘separated genitive’, a grammatical phenomenon whose systematic presence dates back to the early Middle English period (c. 1250), is more deeply rooted in the English language than has been believed, as a similar construction can be attested in a considerable number of Old English texts. The arguments which negate the existence of the separated genitive in Old English are critically reviewed in the study and reassessed in the light of fresh evidence retrieved from a large corpus of texts. The results of the analysis prove that —despite its very low frequency as compared to the flexive genitive— the separated genitive was a viable grammatical option in Old English, and that the syntactic configurations that arose from it probably paved the way to the use of the ‘his genitive’ in the Middle Ages. Keywords: his genitive; separated genitive; Old English; Middle English; possessor doubling; possessive dative; sympathetic dative; York Corpus